2016
DOI: 10.1016/j.phytochem.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Kalkipyrone B, a marine cyanobacterial γ-pyrone possessing cytotoxic and anti-fungal activities

Abstract: Bioassay-guided fractionation of two marine cyanobacterial extracts using the H-460 human lung cancer cell line and the OVC-5 human ovarian cancer cell line led to the isolation of three related α-methoxy-β, β’-dimethyl-γ-pyrones each containing a modified alkyl chain, one of which was identified as the previously reported kalkipyrone and designated kalkipyrone A. The second compound was an analog designated kalkipyrone B. The third was identified as the recently reported yoshipyrone A, also isolated from a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
(27 reference statements)
0
21
0
Order By: Relevance
“…The number of free hydroxyl groups is critical to the antiproliferative effect of the macrocyclic polyketide amantelide A, as its peracetylated derivative was essentially inactive [ 9 ]. This effect was also observed with kalkipyrone B and its acetylated derivative [ 8 ]. These modified products have decreased hydroxyl character.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The number of free hydroxyl groups is critical to the antiproliferative effect of the macrocyclic polyketide amantelide A, as its peracetylated derivative was essentially inactive [ 9 ]. This effect was also observed with kalkipyrone B and its acetylated derivative [ 8 ]. These modified products have decreased hydroxyl character.…”
Section: Discussionmentioning
confidence: 63%
“…Macrocyclic and linear polyketides have been isolated from cyanobacteria with less regularity than NRPS and NRPS-PKS molecules. Still, many of these polyketides have exhibited a diverse array of biological activities [ 8 , 9 , 10 ] and possess highly functionalized structural elements [ 11 , 12 , 13 ] demonstrating the importance of their continued isolation and biological evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…The latter consisted of three methyl groups, eleven methylenes, thirteen methines, and two quaternary carbon atoms with the presence of one aromatic ring. Trycophycin A showed several structural similarities to trichotoxin A and B [ 66 ] while possessing a longer polyketide chain than trichotoxin A with two additional alcohol groups and one additional branched methyl. Trichophycin A showed moderate cytotoxicity against neuro-2A cells and HCT-116 cells with EC 50 values 6.5 ± 1.4 μM and 11.7 ± 0.6 μM, respectively.…”
Section: Chemical Diversity Of Secondary Metabolites From Cyanobacmentioning
confidence: 99%
“…Pyrones are a well-known class of microbial secondary metabolites and are found to have a wide range of biological activities such as anti-inflammatory [ 9 ], anticancer [ 10 ], antimicrobial [ 11 , 12 ], anti-obesity [ 13 , 14 ], and antibiotic activities [ 15 ]. Previous studies on microbial sources have shown that the main producer of α-pyrones is fungi, but α-pyrones are also produced by plants, animals, and bacteria.…”
Section: Resultsmentioning
confidence: 99%